Introduction to research methods and data analysis in the health sciences - Hagger-Johnson, Gareth (London ; New York : Routledge, Taylor & Francis Group, 2014)
"Whilst the 'health sciences' are a broad and diverse area, and includes public health, primary care, health psychology, psychiatry and epidemiology, the research methods and data analysis skills required to analyse them are very similar. Moreover, the ability to appraise and conduct research is emphasised within the health sciences - and students are expected increasingly to do both. Introduction to Research Methods and Data Analysis in the Health Sciences presents a balanced blend of quantitative research methods, and the most widely used techniques for collecting and analysing data in the health sciences. Highly practical in nature, the book guides you, step-by-step, through the research process, and covers both the consumption and the production of research and data analysis. Divided into the three strands that run throughout quantitative health science research - critical numbers, critical appraisal of existing research, and conducting new research"--Provided by publisher.
Includes bibliographical references (pages 294-299) and index.
Catalography
Keywords: Biomedical Research -- methods; Data Interpretation, Statistical; Research Design